2006
DOI: 10.1097/01.brs.0000203707.79269.6a
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar Bony Fusion After Cervical Laminoplasty: Its Characteristics and Relationship With Clinical Results

Abstract: Postoperative interlaminar bony fusion occurred in 53% of patients, with marked frequency at C2/3 after laminoplasty. It did not influence neurologic recovery, but it did reduce the postoperative sagittal ROM of the cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Segmental ROM at C2-3, which is the proximal adjacent segment, showed the most significant decrease during both flexion-extension and rotation. At C2-3, as Iizuka et al 6 suggested, the lifted C-3 lamina appeared to collide with the inferior edge of the C-2 lamina during both extension and rotation (see Videos 1 and 2, which demonstrate the reduction of ROM both in flexion-extension and in rotation by the collision of lifted laminae). We think that this is the mechanism by which the segmental ROM at C2-3 decreased omnidirectionally and that this is one of reasons C2-3 is the level most frequently involved in laminar fusion.…”
Section: Figmentioning
confidence: 96%
See 3 more Smart Citations
“…Segmental ROM at C2-3, which is the proximal adjacent segment, showed the most significant decrease during both flexion-extension and rotation. At C2-3, as Iizuka et al 6 suggested, the lifted C-3 lamina appeared to collide with the inferior edge of the C-2 lamina during both extension and rotation (see Videos 1 and 2, which demonstrate the reduction of ROM both in flexion-extension and in rotation by the collision of lifted laminae). We think that this is the mechanism by which the segmental ROM at C2-3 decreased omnidirectionally and that this is one of reasons C2-3 is the level most frequently involved in laminar fusion.…”
Section: Figmentioning
confidence: 96%
“…However, almost all of these studies assessed neither total cervical ROM nor segmental ROM but only partial cervical flexion-extension ROM (C2-7 angle), using lateral radiographs. [1][2][3][4][5][6]11,13,15,16,18,21,22,26,28 That assessment method is useless when the C-7 vertebra is masked by shoulder girdle shadows. We obtained similar results in our study; we found that C2-7 ROM during flexion-extension decreased significantly by 23% after laminoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative interlaminar bony fusion with reduced cervical ROM has been reported to occur in patients undergoing laminoplasty (Seichi et al 2001, Kawaguchi et al 2003, Iizuka et al 2006). In our modified method with secure anchor fixation, the ROM values were not compromised, which may have been due to the possibility of undergoing early physiotherapy.…”
Section: Discussionmentioning
confidence: 99%